2021
DOI: 10.1109/tasc.2021.3070232
|View full text |Cite
|
Sign up to set email alerts
|

Turn-to-Turn Contact Resistance Measurement of No-Insulation REBCO Pancake Coil: External Field Dependence

Abstract: The characteristics of no-insulation hightemperature superconducting (HTS) manet is dominated by the magnitude of the turn-to-turn contact resistance. A few techniques have been proposed to increase the turn-to-turn contact resistance. The relation between the turn-to-turn contact resistance and the magnet stability has also been investigated in simulations. Although the turn-to-turn contact resistance measurement was only the sudden-discharging method before, we proposed a lowfrequency-AC current (LFAC) metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…where V p and I p are the peak of voltage and current, respectively. Through measurements, the validity of the LFAC method was confirmed under several conditions [28][29][30]. The measurement accuracy was discussed against various frequencies in [31].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…where V p and I p are the peak of voltage and current, respectively. Through measurements, the validity of the LFAC method was confirmed under several conditions [28][29][30]. The measurement accuracy was discussed against various frequencies in [31].…”
Section: Introductionmentioning
confidence: 88%
“…As an alternative method, we have previously proposed a low-frequency AC current (LFAC) method [28]. The LFAC method can measure the contact resistances under different conditions, such as operating current or field dependencies [29,30]. In the LFAC method, an AC current whose frequency satisfies the following condition is applied to an NI REBCO pancake coil:…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have reported that setting only a uniform TTRD in simulation models is not sufficient to accurately predict the behaviour of NI coils in experiments [18,[24][25][26]. In fact, the TTRD of NI coils is affected by various factors including surface condition [27], temperature [12], number of thermal cycles [2] and turn-to-turn contact pressure [1] which is influenced by winding tension [28], thermal stress [28] and electromagnetic force [29]. Some studies [28,[30][31][32][33] have shown that even if the coil is wound with uniform pre-stress, the TTRD of the coil still exhibits a non-uniform distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of contact resistance on the field delay time and quench behaviors of NI coils has been studied by a few research groups [16][17][18]. Recently, the increase of turn-to-turn contact resistance in the high field has been observed in experiments [19][20][21]. The contact resistance is a critical parameter in the development of HTS magnets, and it affects the field delay, thermal stability and total loss of the magnet [18,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The contact resistance is a critical parameter in the development of HTS magnets, and it affects the field delay, thermal stability and total loss of the magnet [18,[22][23][24][25]. Noguchi et al [19] measured the contact resistance of an NI pancake coil in different external fields using the low-frequency AC current method. They found that the contact resistance of the NI coil in an external field of 3 T was much higher than that in an external field of 1 T. Suetomi et al [20] conducted several thermal cycles and charging tests on an intra-layer NI REBCO coil, and they found that there was a significant increase in the contact resistance of the coil after charging tests, particularly after high-field tests.…”
Section: Introductionmentioning
confidence: 99%